Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1007/s12028-010-9330-9
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial Multimodal Monitoring for Acute Brain Injury: A Single Institution Review of Current Practices

Abstract: Collaboration among institutions is necessary to establish practice guidelines for the choice and placement of multimodal monitors. Further advancement in device technology is needed to improve insertion techniques, inter-device compatibility, and device durability. Multimodality data needs to be analyzed to determine the preferable device location.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
60
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 82 publications
(63 citation statements)
references
References 30 publications
(51 reference statements)
1
60
0
1
Order By: Relevance
“…24 Care of patients is increasingly being individualized using multi-modal monitoring to adjust physiological goals, including intracranial pressure (ICP), cerebral perfusion pressure, and PCO 2 or PO 2 targets. [25][26][27] Several observational studies have suggested that an organized, protocol-based approach with emphasis on the prevention of ''secondary'' neurological insults may be associated with improved recovery. [28][29][30][31][32][33][34] Consistent with these developments, the care of neurocritical care patients in our region of Canada has evolved considerably over the past decade.…”
Section: Résumémentioning
confidence: 99%
“…24 Care of patients is increasingly being individualized using multi-modal monitoring to adjust physiological goals, including intracranial pressure (ICP), cerebral perfusion pressure, and PCO 2 or PO 2 targets. [25][26][27] Several observational studies have suggested that an organized, protocol-based approach with emphasis on the prevention of ''secondary'' neurological insults may be associated with improved recovery. [28][29][30][31][32][33][34] Consistent with these developments, the care of neurocritical care patients in our region of Canada has evolved considerably over the past decade.…”
Section: Résumémentioning
confidence: 99%
“…Currently, the assessment of intracranial status for severely injured brain is commonly done with gold standard ICP monitoring alone. Lately, as our understanding on the complex pathophysiology underlying severely injured brain expands, new modalities of brain monitoring emerge, incorporating various brain parameters known as the multimodality monitoring Isa et al, 2003;Stuart et al, 2010).…”
Section: Specific Monitoringmentioning
confidence: 99%
“…While no protocols are available what modalities should be used, it seems wise to choose a multimodal approach. Furthermore, failures of sensors are common, the most frequent complication of brain monitoring was found to be device malfunction or dislodgement [9]. On the other hand, rates of hematoma or infections related to brain monitoring were reported between 3% and 5% in a recent study.…”
mentioning
confidence: 99%